1997
DOI: 10.1002/j.1551-8833.1997.tb08213.x
|View full text |Cite
|
Sign up to set email alerts
|

FPA of selected odorous compounds

Abstract: Flavor profile analysis proves to be a reliable method of evaluating odors in water, especially when performed by well‐trained panelists using familiar descriptors. The odors of 15 organic compounds were evaluated by the flavor profile analysis (FPA) method. The FPA data were well described by the Weber‐Fechner law, as indicated by the R2 values (0.6–0.99). Odor threshold concentrations were obtained and ranged from <0.01 μg/L (geosmin, 2‐methylisoborneol, and 2t,6c‐nonadienal) to 60 μg/L (phenethyl alcohol). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 24 publications
1
44
0
2
Order By: Relevance
“…3 (a). Some typical polyunsaturated fatty acid (PUFA) derivatives, including 2,4-heptadienal, 2,6-nonadienal, and 2,4-decadienal, are reportedly associated with fishy/oily/cucumber odors (Rashash et al, 1997;Hartvigsen et al, 2000). According to previous studies, Dinobryon (Watson et al, 2001;Zhao et al, 2013), Melosira (Wendel and Juttner, 1996), Synura (Wee et al, 1994), and Uroglena (Watson and Satchwill, 2003) can produce these unsaturated aldehydes.…”
Section: Evaluation Of Typical Odorous Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 (a). Some typical polyunsaturated fatty acid (PUFA) derivatives, including 2,4-heptadienal, 2,6-nonadienal, and 2,4-decadienal, are reportedly associated with fishy/oily/cucumber odors (Rashash et al, 1997;Hartvigsen et al, 2000). According to previous studies, Dinobryon (Watson et al, 2001;Zhao et al, 2013), Melosira (Wendel and Juttner, 1996), Synura (Wee et al, 1994), and Uroglena (Watson and Satchwill, 2003) can produce these unsaturated aldehydes.…”
Section: Evaluation Of Typical Odorous Compoundsmentioning
confidence: 99%
“…The OAVs for the detected aldehydes were all below 0.15, except for nonanal (0.20e1.03), which is reportedly associated with fruity odor (Cotsaris et al, 1995), indicating that these compounds might have less impact on fishy odors. However, Rashash et al (1997) revealed that interferences (e.g. masking, antagonism, or synergism) exist among compound mixtures, and subthreshold concentrations of some odorous compounds may contribute to overall perception.…”
Section: Evaluation Of Typical Odorous Compoundsmentioning
confidence: 99%
“…2. OTC has been defined as the odorant concentration corresponding to an FPA intensity of 1 (Rashash et al, 1997;Suffet et al, 2004). Table 1 shows the corresponding OTC value of each city acquired using the Weber-Fechner model.…”
Section: Weber-fechner Plots Of 2-mibmentioning
confidence: 99%
“…Flavor profile analysis (FPA), which uses a minimum of four trained panelists to identify the types and intensities of the odors present in samples (APHA et al, 2005;Rashash et al, 1997), is one of the most popular drinking water odor sensory methods. FPA data can be described using the Weber-Fechner model to relate odor intensity to the logarithm of odorant concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Deste modo, o desenvolvimento de técnicas alternativas para a identificação e quantificação de compostos orgânicos causadores de gosto e odor tem sido consideradas e dentre estas, pode-se citar à utilização do Painel Sensorial (Flavor Profile Analysis), largamente difundido na indústria alimentícia e de bebidas (Bartels et al, 1986;Rashash et al, 1997) …”
Section: Introductionunclassified